PERSEPSI GURU BK TENTANG PELAKSANAAN PEMINATAN PADA KURIKULUM 2013 DI SMA NEGERI 2 BAYANG KABUPATEN PESISIR SELATAN - Sari, Putri Nola (Bimbingan dan Konseling, 2014)
This research is motivated by guidance and counseling teachers in determining the selection of specialization to students based on the demands of the curriculum in 2013 which has been carrying out in accordance with the demands of the curriculum, 2013. Being the focus of this study is the teachers perception of the service implementation specialization guidance and counseling learners to the curriculum in 2013. This research is a descriptive qualitative research. Sampling using purposive random sampling technique. This study described the way in doing service counseling teacher learners specialization in the field as it is about the perception of teachers on the implementation of the guidance and counseling curriculum specialization in 2013. As for the research informants is 3 guidance and counseling teachers, representatives of the curriculum, and principals. Instruments that researchers use in this election is the interview, observation and documentation. This data was tested by performing triangulation after that proceed to conclusion. The results have been analyzed interviews revealed that, guidance and counseling teachers perceptions about the implementation of the curriculum specialization in 2013 at SMAN 2 Regency Bayang West Pesisir, South Coastal District, then the conclusion can be drawn as follows: guidance and counseling teacher perceptions of service specialization of students in the curriculum in 2013, namely in terms of the level of direction specialization learners are already implementing guidance and counseling teacher level and the direction of specialization, in accordance with the procedures specified in the curriculum in 2013, viewed from the aspect of specialization learners, can also be seen from the main measures of service specialization specialization learners and comprehensive services to students who have conducted by SMA 2 Regency Bayang West Pesisir.